El Presupuesto Maestro como herramienta estratégica para la gestión financiera en la Mueblería Capriní del municipio de Palmira (2024)
This degree work focuses on analyzing and highlighting the importance of the "Master Budget" as a strategic tool for financial management, focusing specifically on the context of the Capriní Furniture Store located in the Municipality of Palmira.